2016
DOI: 10.1097/md.0000000000005572
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic perivascular epithelioid cell tumor

Abstract: Rational:Perivascular epithelioid cell tumor (PEComa) is a rare mesenchymal neoplasm which expresses both myogenic and melanocytic markers. PEComas are found in a variety locations in the body, but up to now only approximately 30 cases about hepatic perivascular epithelioid cell tumor are reported in English language worldwide.Patient concerns:A 32-year-old woman was admitted in our hospital with intermittent right upper quadrant pain for 1 month and recent (1 day) progressive deterioration.Diagnoses:Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
1
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
3
9
1
1
Order By: Relevance
“…Hepatic pecomas are rare but increasingly recognized tumors. To date approximately 33 cases of hepatic pecomas have been reported [ [1] , [2] , [3] ].They can occur at any age, although it has been reported that they predominantly affect women aged 30–50 years old [ 11 ]. Hepatic PECOMA may occur as a solitary mass or as multiple lesions, which have been suggested to be associated with tuberous sclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hepatic pecomas are rare but increasingly recognized tumors. To date approximately 33 cases of hepatic pecomas have been reported [ [1] , [2] , [3] ].They can occur at any age, although it has been reported that they predominantly affect women aged 30–50 years old [ 11 ]. Hepatic PECOMA may occur as a solitary mass or as multiple lesions, which have been suggested to be associated with tuberous sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are often asymptomatic. Gastrointestinal symptoms exist when the tumor size cause localized pressure effect [ 1 ]. Imaging diagnosis can be challenging because the quantity of adipose tissue, irregular vessels and smooth muscle cells is various.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conclusion: IHS mimics HCC on imaging and should be considered as a differential diagnosis when a history of splenic trauma or splenectomy is present.Additionally,risk factors for HCC warrant consideration,and if absent,IHS should be considered as a differential.Laparoscopic liver resection can be performed with minimal morbidity and enables definitive diagnosis with histopathological examination and avoids the need for long term surveillance. 1 , H. Mestiri 1 and T. Khalfallah 1 1 Mongi Slim La Marsa, Visceral surgery, and 2 Mongi Slim La Marsa, Gastroenterology, Tunis, Tunisia Background: Treatment of pyogenic liver abscesses (PLA) is not well codified yet. Our aim is to compare treatment modalities of PLA that are antibiotics, percutaneous drainage and surgical drainage.…”
Section: P3103 Intrahepatic Splenosis Mimicking Hepatocellular Carcimentioning
confidence: 99%
“…Results: Liver PEComas were before considered as benign tumors, with surgical treatment in selected cases. The publications in the medical literature of some cases that confirm a malign transformation of AML have made the surgical indications for this pathology a controversial issue, recommending it in exophytic, >5cm or fast growing tumors [1][2] [3]. Conclusion: Nowadays, liver PEComas are considerate as rare tumors with risk of malignancy in some cases, making the surgical intervention the primary treatment.…”
mentioning
confidence: 99%